Estimation of Economic Efficiency and Long-Term Development of Semiconductor Factory on the Basis of Output of Blue Light-Emitting Diodes - Motsnyi, F. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The aim of the study is to estimate the economic efficiency of a semiconductor factory using its output of blue light-emitting diodes. The economic efficiency of a semiconductor factory is analysed. The parameters for profitability or unprofitability of the output of light-emitting diodes are estimated.